Engineering Innovations Vol. 12 - Risa Suryana; Anna Safitri; Noto Susanto Gultom (Trans Tech Publications Ltd, 2025)
The 12th volume of Engineering Innovations accumulated articles that inform readers of the latest research results and engineering solutions in fire retardant materials based on epoxy resin, specific features of wire arc additive manufacturing technology, structures'designing for transportation objects, engineering measurements and free space optical communication. This edition will be useful to a wide range of engineers and researchers in their activities.